ĐÁNH GIÁ TÁC DỤNG KHÁNG SÂU RĂNG CỦA NƯỚC SÚC MIỆNG CHỨA α-MANGOSTIN - Hoàng, Đức Hậu; Võ, Viết Cường; Nguyễn, Vũ Anh; Nguyễn, Thị Mai Phương (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
EVALUATION OF THE ANTI TOOTH DECAY EFFECT OF THE MOUTHWASH CONTAINING α-MANGOSTIN The mouthwash containing 150 mM α-mangostin concentration was created which had inhibiting activities against the acid secretion and biofilm formation by bacterial S. mutans as well as commercial X mouthwash. The final pH value of cultivation medium after using this mouthwash liquid was approximate 4.9, higher than the control sample using ethanol solvent. Our mouthwash product decreases biofilm formation to 32% in comparison with the control sample. The S. mutans inhibiting activity of the mouthwash product remained unchanged after 8 months storage at room temperature.